Gross morphology and adhesion-associated physical properties of Drosophila larval salivary gland glue secretion - Beňo, Milan; Beňová-Liszeková, Denisa; Kostič, Ivan; Šerý, Michal; Mentelová, Lucia; Procházka, Michal; Šoltýs, Ján; Trusinová, Ludmila; Ritomský, Mário; Orovčík, Lubomír; Jerigová, Monika; Velič, Dušan; et al. (Scientific reports, 2024)
One of the major functions of the larval salivary glands (SGs) of many Drosophila species is to produce a massive secretion during puparium formation. This so-called proteinaceous glue is exocytosed into the centrally located lumen, and subsequently expectorated, serving as an adhesive to attach the puparial case to a solid substrate during metamorphosis. Although this was first described almost 70 years ago, a detailed description of the morphology and mechanical properties of the glue is largely missing. Its main known physical property is that it is released as a watery liquid that quickly hardens into a solid cement. Here, we provide a detailed morphological and topological analysis of the solidified glue. We demonstrated that it forms a distinctive enamel-like plaque that is composed of a central fingerprint surrounded by a cascade of laterally layered terraces. The solidifying glue rapidly produces crystals of KCl on these alluvial-like terraces. Since the properties of the glue affect the adhesion of the puparium to its substrate, and so can influence the success of metamorphosis, we evaluated over 80 different materials for their ability to adhere to the glue to determine which properties favor strong adhesion. We found that the alkaline Sgs-glue adheres strongly to wettable and positively charged surfaces but not to neutral or negatively charged and hydrophobic surfaces. Puparia formed on unfavored materials can be removed easily without leaving fingerprints or cascading terraces. For successful adhesion of the Sgs-glue, the material surface must display a specific type of triboelectric charge. Interestingly, the expectorated glue can move upwards against gravity on the surface of freshly formed puparia via specific, unique and novel anatomical structures present in the puparial's lateral abdominal segments that we have named bidentia.
Keywords: Adhesives; Pupa; biologická proměna; kukla; Animals; slinné žlázy; Larva; larva; Salivary Glands; Exocytotic salivary glue secretion; Larval salivary glands; Drosophila; Glue-substrate relationship; Pupariation; Triboelectric series; adheziva; Metamorphosis, Biological; zvířata